Infection and Phytopathological effects of Curvularia lunata in Sorghum - Sharma, Khushboo; Agrawal, Kailash; Jain, Sonal (Journal of Neonatal Surgery, 2025)
A study of 98 seed samples of sorghum procured from 14 locations revealed a high percent incidence of Curvularia lunata. The seeds were categorized into asymptomatic, moderately symptomatic and heavily symptomatic categories to examine the phytopathological effects of C. lunata using the Petri-plate method and test-tube seedling symptom test. The biochemical analysis was also assessed to identify the nutritional values in infected seeds with comparison to the healthy seeds. The percent of asymptomatic, moderately symptomatic and heavily symptomatic seeds (400 seeds/sample) were 36-120, 50-113 and 16-99%, respectively. 200 seeds per sample were sown on moist blotting papers (10 seeds/plate) and on 1% water agar medium in test tubes (1seed/test tube) and incubated at 25±2oC for 12/12 h alternating cycles of light and darkness for up to 7 days and 14 days, respectively. On the 7th and 14th days, seed germination, ungerminated seeds with fungal growth, seedlings with symptoms and mortality were observed. The symptomatic seedling part kept on the fresh PDA plate to isolate C. lunata. The symptoms on seedlings were black spots on shoot and leaf, necrosis and rotting. The ungerminated seeds showed rotting with heavy growth of C. lunata on and around the seeds. The protein, carbohydrates, and lipid contents were decreased in infected seeds as compared to the healthy seeds, but in some infected seeds protein content was increased, may be due to activation of stress proteins. The phenol and tannin contents were comparatively increased to regulate the fungal stress condition. The finding suggests that Curvularia lunata is transferred to the next generations through infected seeds and decreased the nutritional values in sorghum seeds